Pengaruh Latihan Rentang Gerak Ekstremitas Bawah terhadap Keseimbangan Tubuh Lansia di Posyandu Alamanda 99 Kelurahan Jember Lor Kabupaten Jember (The Effect of Range of Motion Exercise at Lower Limb to Elderly Postural Balance in Posyandu Alamanda 99 Jem - Muhammad Athok Fitriyansyah; Tantut Susanto; Hanny Rasni (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Elderly with imbalance is one of the occurrence falls that lead to injury. Range of motionexercises is a cycle activity that improve the function of the limb and mobilization. This studyaimed to the effect of range of motion exercise at lower limb to elderly postural balance inPosyandu Alamanda 99 Jember lor Village District Jember. The design of this study was preexperimental, 16 elderly over 60 years as sample of this study by taking simple randomsampling technique. Postural balance assessment done every sunday for three weeks. Analysisof the data using ANOVA test. The results of data analysis showed p value of 0.002 meansthere was a significant increased in the value of body balance after active range of motionexercise at lower limb. The result of Post Hoc Test showed an increase in the average balancevalue of the most significant after 3 weeks of exercising. Advice of the results study are range ofmotion exercises at lower limb can be performed in the elderly among community and can betaught through elderly activities in integrated health service post.Keywords: Range of motion exercise, postural balance, elderly